Badania Pewnych Reologicznych Własności Elastooptycznych Kilku Żywic Poliestrowych (I) - Pindera, J.T. (Engineering Transactions, 1959)
In the present state of development of photoelastic methods, it is necessary to devote more attention to the investigation of the properties of materials for models, especially for loads of long duration. The influence of loads of long duration on the photoelastic properties of materials was tested by various authors, several measurement methods being used. The tests carried out, usually with beams subjected to pure bending with moments of constant value or prismatic specimens subjected to a progressively increasing load, were confined to the investigation of the optical creep with constant load. Some of the investigations of photo- elastic creep are analyzed in the present paper, and reveal the incompleteness of the investigation methods over the photoelastic properties of materials hitherto employed.For a homogeneous practically one-axial stress field an investigation method and technique is proposed, involving models in the form of slender wedges, stretched by a constant axial force.Methods and technique of tests of creep and optical retardation withperiodic loads are also advanced. The structure and properties of the polyester resins (CR-39 resin, VP-1527 resin and P-6 palatal resin) are analyzed on the basis of the literature.A program is suggested for tests concerning the creep and elasto-plastic retardation with static and periodic loads, in such a manner that the results obtained may be interpreted from the structural and rheological point of view and constitute an introduction to further investigation of photoelastic vibro-creeping.